Epidaus wangi (Hemiptera: Heteroptera: Reduviidae), a new assassin bug from Tibet, China - Chen, Zhuo; Zhu, Guangxiang; Wang, Jianyun; Cai, Wanzhi (Zootaxa, 2016)
Epidaus wangi Chen, Zhu, Wang & Cai, sp. nov. (Hemiptera: Heteroptera: Reduviidae: Harpactorinae) from Tibet, China, is described and illustrated based on male and female specimens. The new species is morphologically similar to E. tuberosus Yang, 1940. The new species represents the first record of Epidaus species from Tibet.